BUSINESS STUDIES TEACHERS' PERCEPTION OF THE EXTENT TO WHICH PRINCIPALS ADOPT THREE ADMINISTRATIVE STYLES IN SECONDARY SCHOOLS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study was intended to establish the business studies teachers' perception of theextent in which principals in Anambra State secondary schools adopt three administrativestyles in their schools. Three research questions and four null hypotheses guided the study.Descriptive survey design was adopted and a population of 295 business studies teachers wasused for the study. A 40-item validated questionnaire, structured on a 5-point responseoptions with 0.96 reliability coefficient was used for data collection. Data were analyzed withthe arithmetic mean, standard deviation andz-test at 0.05 level of significance. Findingsrevealed that secondary school principals in the area of study adopt the democraticadministrative style to a high extent and adopt autocratic and laissez-faire administrativestyles to a low extent. Experience did not significantly affect respondents' opinions but genderand school location did. Based on the findings, it was concluded that secondary schoolteachers in Anambra State Nigeria should be well equipped on infrastructural facilities inorder to perform better in decision making. It was recommended, among others, that theprincipals should continue to adopt democratic administrative style and also encourage theircounterparts in other states to emulate them in order to enhance teacher performance.
Keywords: Democratic administrative style, autocratic administrative style, laissez faire administrative style